Positive electrode active material and preparation method thereof, composite positive electrode and aqueous zinc ion battery

A dehydration condensation reaction between aminoquinone and carbonyl compounds creates a positive electrode active material with enhanced zinc storage sites, addressing the limitations of traditional materials and achieving higher capacity and stability in aqueous zinc-ion batteries.

CN115483387BInactive Publication Date: 2024-12-20SHIHEZI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211315580.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-26
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries face safety concerns, high cost, and resource limitations, while inorganic positive electrode materials for aqueous zinc-ion batteries suffer from structural collapse due to zinc ion insertion/extraction, and organic quinone-based compounds have low specific capacity.

Method used

A method involving a dehydration condensation reaction between aminoquinone and carbonyl-containing compounds to form a positive electrode active material with C=O and C=N active sites, enhancing zinc storage density.

Benefits of technology

The resulting aqueous zinc-ion batteries exhibit higher specific capacity and improved cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115483387B_ABST
    Figure CN115483387B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of zinc ion batteries, and specifically relates to a positive electrode active material and a preparation method thereof, a composite positive electrode and an aqueous zinc ion battery. The present invention provides a preparation method of a positive electrode active material, comprising the following steps: mixing a first organic compound and a second organic compound, and subjecting the mixture to a dehydration condensation reaction to obtain the positive electrode active material; the first organic compound comprises an aminoquinone compound; and the functional group of the second organic compound comprises a carbonyl group. The aqueous zinc ion battery prepared from the positive electrode active material provided by the present invention has a high specific capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zinc ion batteries, and in particular relates to a positive electrode active material and a preparation method thereof, a composite positive electrode and an aqueous zinc ion battery. Background Art

[0002] Due to the use of traditional fossil fuels, environmental pollution is becoming increasingly serious, and people's demand for clean energy is becoming more and more urgent. Electrical energy storage is a mature method of storing clean energy. At present, lithium-ion batteries are widely used in portable electronic products, biomedical devices and new generation electric vehicles. However, due to the safety, high cost and limited lithium resources of lithium-ion batteries, there is an urgent need to develop new energy storage devices to replace lithium-ion batteries.

[0003] Aqueous zinc-ion batteries use zinc metal, which is abundant in resources on Earth, as the negative electrode and use aqueous electrolytes with high ionic conductivity. They have the advantages of high safety, environmental protection, high energy density and high Coulomb efficiency, and have become a hot topic in energy research. The selection of positive electrode materials plays a vital role in achieving high specific capacity and long cycle life of aqueous zinc-ion batteries.

[0004] Traditional positive electrode materials are mainly inorganic electrode materials, including manganese-based oxides, vanadium-based derivatives or Prussian blue analogs. Inorganic electrode materials have the advantages of high capacity, high energy density, and high power density, but due to resource shortages, environmental pollution, complex synthesis processes, and high energy consumption, the further improvement of battery performance is limited. In addition, during the charge and discharge cycle, hydrated Zn 2+ and H + The continuous insertion / extraction of inorganic materials often leads to the collapse of the structure of inorganic materials, reducing the cycle stability of the battery.

[0005] In recent years, some redox-active organic compounds, such as small molecular quinone compounds containing conjugated carbonyl groups, can effectively buffer hydrated Zn due to their flexible skeletons. 2+ and H + The volume change caused by insertion / extraction shows good cycle stability. However, the zinc ion batteries prepared from small molecule quinone-based compounds still have the defect of low specific capacity. Summary of the invention

[0006] The object of the present invention is to provide a positive electrode active material and a preparation method thereof, a composite positive electrode and an aqueous zinc ion battery. The aqueous zinc ion battery prepared from the positive electrode active material provided by the present invention has a higher specific capacity.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a positive electrode active material, comprising the following steps:

[0009] Mixing the first organic compound and the second organic compound, and subjecting the mixture to a dehydration condensation reaction, to obtain the positive electrode active material;

[0010] The first organic compound includes an aminoquinone compound;

[0011] The functional group of the second organic compound includes a carbonyl group.

[0012] Preferably, the aminoquinone compound includes one or more of 1,2-diaminoanthraquinone, 1,2-diaminonaphthoquinone, 2-amino-1,4-naphthoquinone, 2,3,5,6-tetra(amino)benzoquinone, 2-aminoanthraquinone, 2,6-diaminoanthraquinone, 1-aminoanthraquinone-2-carboxylic acid, 1-hydroxy-4-aminoanthraquinone and 1,5-dihydroxy-4,8-diaminoanthraquinone.

[0013] Preferably, the second organic compound includes quinone compounds and / or ketone compounds.

[0014] Preferably, the quinone compound includes one or more of 2,5-dihydroxy-1,4-benzoquinone, tetrahydroxy-1,4-benzoquinone, 2,5-dihydroxy-3,6-dichlorobenzoquinone, anthraquinone and phenanthrenequinone;

[0015] The ketone compound includes one or more of cyclohexanehexaone, cyclopentanepentone, 3,4-dihydroxy-3-cyclobutene-1,2-dione, and 4,5-dihydroxy-4-cyclopentene-1,2,3-trione.

[0016] Preferably, the molar ratio of the first organic compound to the second organic compound is 1-6:1-4.

[0017] Preferably, the temperature of the dehydration condensation reaction is 100-200° C., the heating rate to the dehydration condensation reaction temperature is 1-5° C. / min, and the time is 2-8 hours.

[0018] The present invention also provides a positive electrode active material prepared by the preparation method described in the above technical solution.

[0019] The present invention also provides a composite positive electrode, comprising a current collector and a positive electrode material loaded on the current collector; the positive electrode material comprises a positive electrode active material, a conductive agent and a binder, and the positive electrode active material is the positive electrode active material described in the above technical scheme or the positive electrode active material prepared by the preparation method described in the above technical scheme.

[0020] Preferably, the mass ratio of the positive electrode active material, the conductive agent and the binder is (3-9): (0.5-6): (0.5-1).

[0021] The present invention also provides an aqueous zinc ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is the composite positive electrode described in the above technical solution.

[0022] The present invention provides a method for preparing a positive electrode active material, comprising the following steps: mixing a first organic compound and a second organic compound, and subjecting the mixture to a dehydration condensation reaction to obtain the positive electrode active material; the first organic compound comprises an aminoquinone compound; and the functional group of the second organic compound comprises a carbonyl group. The present invention utilizes -NH2 in the aminoquinone compound and the carbonyl group in the second compound to undergo dehydration condensation to generate C=N, so that the positive electrode active material obtained by the present invention contains two active sites, C=O and C=N, thereby increasing the density of zinc storage sites of the positive electrode active material, and thereby increasing the specific capacity of the aqueous zinc ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the infrared spectrum of the positive electrode active material obtained in Example 1;

[0024] Figure 2 The charge and discharge curve of the aqueous zinc ion battery obtained in Example 1 at a voltage range of 0.2 to 1.7 V and a current density of 50 mA / g;

[0025] Figure 3 The charge and discharge curve of the aqueous zinc ion battery obtained in Example 1 at a voltage range of 0.2 to 1.5 V and a current density of 50 mA / g;

[0026] Figure 4 The cycle curve of the aqueous zinc ion battery obtained in Example 2 at a voltage range of 0.2 to 1.5 V and a current density of 50 mA / g;

[0027] Figure 5 This is the cycle curve of the aqueous zinc ion battery obtained in Example 3 at a voltage range of 0.2 to 1.5 V and a current density of 50 mA / g. DETAILED DESCRIPTION

[0028] The present invention provides a method for preparing a positive electrode active material, comprising the following steps:

[0029] Mixing the first organic compound and the second organic compound, and subjecting the mixture to a dehydration condensation reaction, to obtain the positive electrode active material;

[0030] The first organic compound includes an aminoquinone compound;

[0031] The functional group of the second organic compound includes a carbonyl group.

[0032] In the present invention, unless otherwise specified, all raw materials are commercially available products well known to those skilled in the art.

[0033] In the present invention, the aminoquinone compound preferably includes one or more of 1,2-diaminoanthraquinone, 1,2-diaminonaphthoquinone, 2-amino-1,4-naphthoquinone, 2,3,5,6-tetra(amino)benzoquinone, 2-aminoanthraquinone, 2,6-diaminoanthraquinone, 1-aminoanthraquinone-2-carboxylic acid, 1-hydroxy-4-aminoanthraquinone and 1,5-dihydroxy-4,8-diaminoanthraquinone; when the aminoquinone compound is two or more of the above-mentioned options, the present invention has no special limitation on the ratio of the specific substances, and they can be mixed in any ratio.

[0034] In the present invention, the second organic compound preferably includes quinone compounds and / or ketone compounds. In the present invention, the quinone compounds preferably include one or more of 2,5-dihydroxy-1,4-benzoquinone, tetrahydroxy-1,4-benzoquinone, 2,5-dihydroxy-3,6-dichlorobenzoquinone, anthraquinone and phenanthrenequinone; the ketone compounds preferably include one or more of cyclohexanehexaone, cyclopentapentaone, 3,4-dihydroxy-3-cyclobutene-1,2-dione, 4,5-dihydroxy-4-cyclopentene-1,2,3-trione; when the second organic compound is two or more of the above-mentioned options, the present invention has no special restrictions on the ratio of specific substances, and they can be mixed in any proportion.

[0035] In the present invention, the molar ratio of the first organic compound to the second organic compound is preferably 1-6:1-4, and more preferably 2-5:2-3.

[0036] In the present invention, the mixing method is preferably grinding. The present invention has no particular limitation on the grinding process, and the grinding process can be performed using a process well known to those skilled in the art. In the present invention, the grinding is preferably performed in a mortar.

[0037] In the present invention, the temperature of the dehydration condensation reaction is preferably 100-200°C, more preferably 120-180°C, and more preferably 150-160°C; the heating rate to the dehydration condensation reaction temperature is preferably 1-5°C / min, more preferably 2-4°C / min; the time is preferably 2-8h, more preferably 3-7h, and more preferably 4-6h.

[0038] In the present invention, the dehydration condensation reaction is preferably carried out under a nitrogen atmosphere.

[0039] In the present invention, the dehydration condensation reaction is preferably carried out in a tube furnace.

[0040] After the dehydration condensation reaction is completed, the present invention also preferably includes post-treatment of the obtained product; the post-treatment preferably includes ethanol washing and drying. The present invention has no special limitation on the process of ethanol washing and drying, and can be carried out using a process well known to those skilled in the art.

[0041] The present invention also provides a positive electrode active material prepared by the preparation method described in the above technical solution. In the present invention, the positive electrode active material includes two active sites, C=O and C=N.

[0042] The present invention also provides a composite positive electrode, comprising a current collector and a positive electrode material loaded on the current collector; the positive electrode material comprises a positive electrode active material, a conductive agent and a binder; the positive electrode active material is the positive electrode active material described in the above technical scheme or the positive electrode active material prepared by the preparation method described in the above technical scheme.

[0043] In the present invention, the current collector preferably includes a stainless steel mesh, a stainless steel foil, a titanium mesh, a titanium foil, a porous stainless steel belt, a carbon cloth, a carbon mesh or a carbon felt.

[0044] In the present invention, the positive electrode material includes a positive electrode active material, a conductive agent and a binder. In the present invention, the conductive agent preferably includes a first conductive agent and / or a second conductive agent; the first conductive agent preferably includes Ketjen black and / or acetylene black; the second conductive agent preferably includes one or more of carbon nanotubes, graphene, Mxene two-dimensional materials and carbon fibers. In the present invention, when the conductive agent preferably includes a first conductive agent and a second conductive agent, the mass percentage of the first conductive agent is preferably 5 to 95%.

[0045] In the present invention, the mass ratio of the positive electrode active material, the conductive agent and the binder is preferably (3-9): (0.5-6): (0.5-1), more preferably (4-8): (1.0-5.0): (0.6-0.9), and more preferably (5-7): (2.0-4.0): (0.7-0.8). In the present invention, the loading amount of the positive electrode material on the current collector is preferably 1.5-2.0 mg / cm 2 .

[0046] In the present invention, the method for preparing the composite positive electrode preferably comprises the following steps:

[0047] Mixing a positive electrode active material, a conductive agent, a binder and a polar solvent to obtain a slurry;

[0048] The slurry is coated on the surface of the current collector and dried to obtain the composite positive electrode.

[0049] In the present invention, the polar solvent preferably includes one or more of N-methylpyrrolidone, water and ethanol. The present invention has no particular limitation on the amount of the polar solvent added, and any amount known to those skilled in the art can be used.

[0050] In the present invention, the mixing process is preferably:

[0051] mixing the positive electrode active material and the conductive agent in a primary manner to obtain a primary mixture;

[0052] The binder and the polar solvent are mixed in a secondary manner to obtain a secondary mixture;

[0053] The primary mixture and the secondary mixture are tertiary mixed.

[0054] In the present invention, the primary mixing method is preferably grinding. The present invention has no particular limitation on the grinding process, and the grinding process can be performed using a process well known to those skilled in the art. In the present invention, the grinding is preferably performed in a mortar.

[0055] The present invention has no particular limitation on the process of the secondary mixing, and any method known to those skilled in the art may be adopted.

[0056] In the present invention, the three-stage mixing method is preferably grinding. The present invention has no special limitation on the grinding process, and the grinding process can be carried out by a process well known to those skilled in the art. In the present invention, the grinding is preferably carried out in a mortar.

[0057] The present invention has no particular limitation on the coating process, and the coating process may be carried out using a process well known to those skilled in the art.

[0058] In the present invention, the drying temperature is preferably 60 to 120° C., more preferably 70 to 110° C., and more preferably 80 to 100° C.; the drying time is preferably 8 to 12 h, and more preferably 9 to 10 h.

[0059] In the present invention, the diameter of the composite positive electrode is preferably 10 mm. In a specific embodiment of the present invention, the composite positive electrode with a diameter of 10 mm is preferably obtained by cutting after drying.

[0060] The present invention also provides an aqueous zinc ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is the composite positive electrode described in the above technical solution.

[0061] In the present invention, the negative electrode preferably comprises metal zinc foil or zinc alloy. In the present invention, the diaphragm preferably comprises water filter paper, proton exchange membrane or glass fiber filter paper.

[0062] In the present invention, the electrolyte is preferably an aqueous solution containing a zinc salt or a polyvinyl alcohol hydrogel containing a zinc salt. In the present invention, the zinc salt preferably includes one or more of Zn(CF3SO3)2, ZnSO4, Zn(NO3)2, ZnCl2 and Zn(CH3COO)2. In the present invention, the molar concentration of the zinc salt in the electrolyte is preferably 1 to 3 mol / L. The present invention has no special limitation on the preparation method of the electrolyte, and the method well known to those skilled in the art can be used.

[0063] The present invention has no special limitation on the assembly method of the battery, and the battery can be assembled in the order of the positive electrode shell, the positive electrode, the electrolyte, the separator, the negative electrode, the gasket, the spring and the negative electrode shell. The present invention has no special limitation on the types of the positive electrode shell, the gasket, the spring and the negative electrode shell, and those known to those skilled in the art can be used. In the present invention, the assembly is preferably carried out in an air atmosphere.

[0064] In order to further illustrate the present invention, a positive electrode active material and a preparation method thereof, a composite positive electrode and an aqueous zinc ion battery provided by the present invention are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0065] Example 1

[0066] Weigh 2 mmol of 1,2-diaminoanthraquinone and 0.5 mmol of 2,5-dihydroxy-1,4-benzoquinone, put them in a mortar and grind and mix them. Put the obtained mixture into a tube furnace, introduce nitrogen, and heat it to 180°C at a heating rate of 2°C / min for dehydration condensation reaction for 5 hours. After the reaction is completed, wash the obtained product with ethanol and vacuum dry it to obtain a positive electrode active material;

[0067] 60 mg of positive electrode active material, 20 mg of Ketjen black and 10 mg of carbon nanotubes were put into a mortar for grinding and mixing to obtain a primary mixture; 10 mg of polyvinylidene fluoride and 0.5 mL of N-methylpyrrolidone were mixed to obtain a secondary mixture; the primary mixture and the secondary mixture were mixed and ground to obtain a slurry; the obtained slurry was coated on a stainless steel mesh with a glass rod, and then placed in a vacuum drying oven and dried at 80°C for 12 hours, and a composite positive electrode with a diameter of 10 mm was obtained after cutting (the loading amount of the positive electrode material on the composite positive electrode was 1.6 mg / cm 2 );

[0068] An aqueous zinc ion battery is obtained by assembling a positive electrode shell, a composite positive electrode, a 1 mol / L Zn(CF3SO3)2 aqueous electrolyte, a glass fiber separator, a zinc foil, a gasket, a shrapnel, and a negative electrode shell in the order of the positive electrode shell in air.

[0069] Example 2

[0070] Weigh 2 mmol of 1,2-diaminoanthraquinone and 0.5 mmol of 2,5-dihydroxy-1,4-benzoquinone, put them in a mortar and grind and mix them. Put the obtained mixture into a tube furnace, introduce nitrogen, and heat it to 180°C at a heating rate of 2°C / min for dehydration condensation reaction for 5 hours. After the reaction is completed, wash the obtained product with ethanol and vacuum dry it to obtain a positive electrode active material;

[0071] 60 mg of positive electrode active material and 30 mg of Ketjen black were put into a mortar for grinding and mixing to obtain a primary mixture; 10 mg of polyvinylidene fluoride and 1.5 mL of N-methylpyrrolidone were mixed to obtain a secondary mixture; the primary mixture and the secondary mixture were mixed and ground to obtain a slurry; the obtained slurry was coated on a stainless steel mesh with a glass rod, and then placed in a vacuum drying oven and dried at 80°C for 12 hours, and cut to obtain a composite positive electrode with a diameter of 10 mm (the loading amount of the positive electrode material on the composite positive electrode was 1.6 mg / cm 2 );

[0072] A positive electrode shell, a composite positive electrode, a 1 mol / L Zn(CF3SO3)2 aqueous solution, a glass fiber separator, a zinc foil, a gasket, a shrapnel, and a negative electrode shell are assembled in air in this order to obtain an aqueous zinc ion battery.

[0073] Example 3

[0074] Weigh 2 mmol of 1,2-diaminoanthraquinone and 0.5 mmol of 2,5-dihydroxy-1,4-benzoquinone, put them in a mortar and grind and mix them. Put the obtained mixture into a tube furnace, introduce nitrogen, and heat it to 180°C at a heating rate of 2°C / min for dehydration condensation reaction for 5 hours. After the reaction is completed, wash the obtained product with ethanol and vacuum dry it to obtain a positive electrode active material;

[0075] 60 mg of positive electrode active material, 20 mg of Ketjen black and 10 mg of carbon nanotubes were put into a mortar for grinding and mixing to obtain a primary mixture; 10 mg of polyvinylidene fluoride and 0.5 mL of N-methylpyrrolidone were mixed to obtain a secondary mixture; the primary mixture and the secondary mixture were mixed and ground to obtain a slurry; the obtained slurry was coated on a stainless steel mesh with a glass rod, and then placed in a vacuum drying oven and dried at 80°C for 12 hours, and a composite positive electrode with a diameter of 10 mm was obtained after cutting (the loading amount of the positive electrode material on the composite positive electrode was 1.6 mg / cm 2 );

[0076] An aqueous zinc ion battery was obtained by assembling a positive electrode shell, a composite positive electrode, a 1 mol / L Zn(CF3SO3)2 polyvinyl alcohol hydrogel electrolyte, a glass fiber separator, a zinc foil, a gasket, a shrapnel, and a negative electrode shell in the order of the positive electrode shell.

[0077] Performance Testing

[0078] Test Example 1

[0079] The positive electrode active material obtained in Example 1 was subjected to infrared spectrum test; the obtained test curve is as follows: Figure 1 As shown, from Figure 1 It can be seen that the positive electrode active material obtained in this example contains characteristic peaks of C=O and C=N bonds.

[0080] Test Example 2

[0081] The aqueous zinc ion battery obtained in Example 1 was subjected to charge-discharge cycle and CV tests on a Sunway battery test system and an electrochemical workstation. The voltage test range was 0.2 to 1.7 V and the current density was 50 mA·g -1 The charge-discharge curves are as follows: Figure 2 shown; from Figure 2 It can be seen that the first cycle charging capacity is 191mAh g -1 After 5 cycles, the battery's charge capacity is 185 mAh g -1 .

[0082] Test Example 3

[0083] The aqueous zinc ion battery obtained in Example 1 was subjected to charge-discharge cycle and CV tests on a Sunway battery test system and an electrochemical workstation. The voltage test range was 0.2 to 1.5 V and the current density was 50 mA·g -1 The charge and discharge curves obtained are as follows Figure 3 shown; from Figure 3 It can be seen that the first cycle charging capacity is 59mAh g -1 After 25 cycles, the battery's charge capacity is 158 mAh g -1 When the battery is cycled to 100 times, the specific charge capacity is 131 mAh g -1 , showing good cycle stability.

[0084] Test Example 4

[0085] The aqueous zinc ion battery obtained in Example 2 was subjected to charge-discharge cycle and CV tests on a Sunway battery test system and an electrochemical workstation. The voltage test range was 0.2 to 1.5 V and the current density was 50 mA·g -1 The cycle curve obtained is as follows Figure 4 shown; from Figure 4 It can be seen that the battery's charge capacity is 117 mAh g when the cycle reaches 100 cycles. -1 .

[0086] Test Example 5

[0087] The aqueous zinc ion battery obtained in Example 3 was subjected to charge-discharge cycle and CV tests on a Sunway battery test system and an electrochemical workstation. The voltage test range was 0.2 to 1.5 V and the current density was 50 mA g -1 The cycle curve obtained is as follows Figure 5 shown; from Figure 5 It can be seen that the battery's charge capacity is 128 mAh g when the cycle reaches 100 cycles. -1 , showing excellent electrochemical performance.

[0088] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing an aqueous zinc ion battery, characterized in that: The steps are: Weigh 2 mmol of 1,2-diaminoanthraquinone and 0.5 mmol of 2,5-dihydroxy-1,4-benzoquinone, put them in a mortar for grinding and mixing; put the obtained mixture into a tube furnace, introduce nitrogen, and heat it to 180° C. at a heating rate of 2° C. / min for dehydration condensation reaction for 5 hours. After the reaction is completed, wash the obtained product with ethanol and then vacuum dry it to obtain a positive electrode active material; 60 mg of positive electrode active material, 20 mg of Ketjen black and 10 mg of carbon nanotubes were put into a mortar for grinding and mixing to obtain a primary mixture; 10 mg of polyvinylidene fluoride and 0.5 mL of N-methylpyrrolidone were mixed to obtain a secondary mixture; the primary mixture and the secondary mixture were mixed and ground to obtain a slurry; the obtained slurry was coated on a stainless steel mesh with a glass rod, and then placed in a vacuum drying oven and dried at 80°C for 12 hours, and cut into a 10 mm diameter and a loading of 1.6 mg / cm 2 Composite positive electrode; The aqueous zinc ion battery is obtained by assembling a positive electrode shell, a composite positive electrode, a 1 mol / L Zn(CF3SO3)2 aqueous electrolyte, a glass fiber separator, a zinc foil, a gasket, a shrapnel, and a negative electrode shell in the order of the positive electrode shell and the shrapnel.